1999
DOI: 10.1002/j.0022-0337.1999.63.5.tb03285.x
|View full text |Cite
|
Sign up to set email alerts
|

Using choice‐based conjoint to determine the relative importance of dental benefit plan attributes

Abstract: The purpose of this study was to use conjoint analysis to determine the importance of specific dental benefit plan features for University of Iowa (UI) staff and to build a model to predict enrollment. From a random sample of 2000 UI staff, 40 percent responded (N = 773). The survey instrument was developed using seven attributes (five dental benefit plan features and two facility characteristics) each offered at three levels (e.g., premium = $20, $15, $10/month). Pilot testing was used to find a realistic ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…35 Conjoint analysis has been used several times in order to analyze consumers decision making process in choosing health insurance as well as long term private insurance and dental insurance. [36][37][38][39][40][41][42] These research studies have demonstrated several benefits of using conjoint analysis in evaluating consumer preferences in choosing health plans. For example, these studies have demonstrated that some of the most important attributes consumers consider when choosing health care plans include premiums, freedom in choosing physicians, copayments for physicians vists, copayments for medications, freedom in choosing hospitals, and inclusion or exclusion of vision and dental coverage and strongly prefer plans which have high maximum liability.…”
Section: Overview Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…35 Conjoint analysis has been used several times in order to analyze consumers decision making process in choosing health insurance as well as long term private insurance and dental insurance. [36][37][38][39][40][41][42] These research studies have demonstrated several benefits of using conjoint analysis in evaluating consumer preferences in choosing health plans. For example, these studies have demonstrated that some of the most important attributes consumers consider when choosing health care plans include premiums, freedom in choosing physicians, copayments for physicians vists, copayments for medications, freedom in choosing hospitals, and inclusion or exclusion of vision and dental coverage and strongly prefer plans which have high maximum liability.…”
Section: Overview Of Analysismentioning
confidence: 99%
“…35 Simulation procedures have been performed in several cases to simulate both current and hypothetical health plans performance in the market place. 36,42 Studies have shown that the data gathered from conjoint analysis studies is reliable in predicting the market share of different types of insurance plans which are currently on the market when used in simulations. 36,42 Subgroup analysis on secondary variables can also be performed so that differential preferences in between groups which are moderated by demographic variables may be analyzed.…”
Section: Overview Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Conjoint analysis can better model actual decision making because it requires respondents to make trade-offs in a holistic context, as opposed to others surveys which do not impose a resource constraint; for example, respondents can rate all attributes as ''extremely important'' without having to evaluate trade-offs. 196,197,198 Conjoint analysis, which was developed originally in economic and marketing research, was based on the theory that decision options can be described by sets of attributes or factors, each made up of different levels. 199,200 The relative value that professionals attach to different factors can be estimated by constructing a series of hypothetical scenarios made up of these factors at different levels and asking professionals to rate, rank, or make choices within a set of hypothetical options.…”
Section: Introductionmentioning
confidence: 99%
“…[203][204][205][206][207][208] In spite of this, the use of conjoint analysis is still rare in dental research. [196][197][198] One of the applications where conjoint analysis was used in dental research assessed the determinants of dentists' decisions to initiate a particular restorative treatment, dental implants. This study found disagreement between what dentists say to be important (self-reported task) and the factors they actually use to judge the suitability of implant treatment (hypothetical scenarios based on a conjoint task).…”
Section: Introductionmentioning
confidence: 99%